Effects of radiant exposure and wavelength spectrum of light-curing units on chemical and physical properties of resin cements - Adriano Fonseca Lima; Stephanie Ellen Ferreira Formaggio; Lígia França Aires Zambelli; Alan Rodrigo Muniz Palialol; Giselle Maria Marchi; Cintia Helena Coury Saraceni; Marcelo Tavares de Oliveira (Korean Academy of Conservative Dentistry, 2016)
Objectives In this study, we evaluated the influence of different radiant exposures provided by single-peak and polywave light-curing units (LCUs) on the degree of conversion (DC) and the mechanical properties of resin cements. Materials and Methods Six experimental groups were established for each cement (RelyX ARC, 3M ESPE; LuxaCore Dual, Ivoclar Vivadent; Variolink, DMG), according to the different radiant exposures (5, 10, and 20 J/cm2) and two LCUs (single-peak and polywave). The specimens were made (7 mm in length × 2 mm in width × 1 mm in height) using silicone molds. After 24 hours of preparation, DC measurement was performed using Fourier transform infrared spectrometry. The same specimens were used for the evaluation of mechanical properties (flexural strength, FS; elastic modulus, E) by a three-point bending test. Data were assessed for normality, after which two-way analysis of variance (ANOVA) and post hoc Tukey's test were performed. Results No properties of the Variolink cement were influenced by any of the considered experimental conditions. In the case of the RelyX ARC cement, DC was higher when polywave LCU was used; FS and E were not influenced by the conditions evaluated. The LuxaCore cement showed greater sensitivity to the different protocols. Conclusions On the basis of these results, both the spectrum of light emitted and the radiant exposure used could affect the properties of resin cements. However, the influence was material-dependent.